Designing Open Trip Strategies for the Development of Tourism in Sumber Jaya Village, Pandeglang Regency, Banten - Azzaki, Mahmud Wahdi; Wihardi, Doddy; Jati, Rocky Prasetyo (Transpublika Publisher, 2025)
Sumber Jaya Village possesses significant tourism potential but faces key challenges, including limited community involvement in tourism management, inadequate digital marketing skills within the local Tourism Awareness Group (POKDARWIS), and low destination visibility. This study examines the implementation of the Open Trip model as a strategy for developing community-based tourism in Sumber Jaya Village, Sumur District, Pandeglang, Banten. Despite its rich natural and cultural tourism potential, the village faces challenges related to limited digital promotion capacity and low community involvement in tourism management. This research employs an Integrated Research Approach combined with Participatory Action Research (PAR), involving field observations, semi-structured interviews with members of the Tourism Awareness Group (POKDARWIS), and community-based digital content creation training. The findings indicate that the integration of the Open Trip model with digital marketing strategies through social media platforms such as Instagram and TikTok increases destination visibility and enhances community participation in tourism promotion. The Open Trip strategy enables the development of flexible, affordable, and socially engaging tourism packages that align with the preferences of young travelers. Furthermore, empowering POKDARWIS members to actively produce and manage promotional content increases community involvement and fosters a sense of ownership over tourism development. This approach contributes to increased tourist visits and a more equitable distribution of economic benefits within the village. Overall, the study demonstrates that integrating the Open Trip model with community-based digital marketing aligns with Community-Based Tourism (CBT) principles and provides a practical and inclusive framework for sustainable rural tourism development.